A new species of the hairy crab genus Pilumnus (Decapoda: Brachyura: Pilumnidae) from Belize - Magalhães, Tatiana; Felder, Darryl L. (Zootaxa, 2019)
A new species of the pilumnid crab genus Pilumnus Leach, 1815, P. mantelattoi n. sp., is described and illustrated on the basis of a single ovigerous female specimen from Belize, bordering the northwestern Caribbean Sea. The holotype, an ovigerous female, was taken from an epifaunal accumulation of sponges, ascidians, and hydroids on red mangrove roots suspended in the water column. Superficially resembling Pilumnus floridanus Stimpson, 1871, with which it occurs sympatrically, it is distinguished from this and all other known western Atlantic species on the basis of both morphology and molecular markers.